Kedudukan Polis Asuransi Jiwa dalam Hukum Waris: Analisis terhadap Uang Pertanggungan Polis Asuransi Jiwa dalam Hukum Waris - Leba, Julio Leonardo; Adjie, Habib (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2024)
Our lives are filled with various kinds of risks that can occur at any time, one of which is the risk of death which can come to us all at any time. Some people are trying to find solutions so that when the risk of death occurs, the family left behind will still have the same economic capacity so that the family can continue to have a good quality and standard of life. This research aims to analyze the position of life insurance policies in Indonesian inheritance law. This research is included in normative juridical legal research or literature. This type of research is descriptive in nature and relies on secondary data collected using library study techniques. Based on this study, it is concluded that life insurance funds obtained as a result of an event or death are not inherited assets. Payment of the policy insurance money is given to the beneficiaries whose names are listed in the life insurance policy.